2020
DOI: 10.3390/rs13010076
|View full text |Cite
|
Sign up to set email alerts
|

Underwater Topography Detection and Analysis of the Qilianyu Islands in the South China Sea Based on GF-3 SAR Images

Abstract: Shallow sea underwater topography plays an important role in the development of islands and reefs. The Qilianyu Islands, located in Xisha, South China Sea, are a key area for the development and utilization of the South China Sea. Compared with traditional underwater topography detection methods, synthetic aperture radar (SAR) has the advantages of low cost, short time consumption, and the large-scale detection of shallow water topography. The GF-3 satellite is the first SAR satellite launched by China, and it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…According to their causes, the undulation of a rough sea surface can be divided into swell wave and wind wave, which generate different characteristics, such as wave crest lines and wave periods. [19,20] Existing researches of underwater acoustic propagation mainly focus on wind waves, whereas swell waves are rarely considered. On the northern continental slope of the South China Sea, experiments showed that swell waves have a strong influence on the acoustic propagation in the surface sound channel.…”
Section: Introductionmentioning
confidence: 99%
“…According to their causes, the undulation of a rough sea surface can be divided into swell wave and wind wave, which generate different characteristics, such as wave crest lines and wave periods. [19,20] Existing researches of underwater acoustic propagation mainly focus on wind waves, whereas swell waves are rarely considered. On the northern continental slope of the South China Sea, experiments showed that swell waves have a strong influence on the acoustic propagation in the surface sound channel.…”
Section: Introductionmentioning
confidence: 99%
“…Since the wavelength range of the electromagnetic signals used by SAR is centimeter to meter, SAR can effectively penetrate concealed objects and clouds [6][7][8][9][10]. In addition, SAR is not affected by illumination conditions and can operate under all-weather, all-day conditions, which is currently an important means of remote sensing observation in many applications [11][12][13][14][15]. Nevertheless, they are more difficult to interpret by human vision than optical images.…”
Section: Introductionmentioning
confidence: 99%
“…With the continuous development of remote sensing technology, optical remote sensing data and synthetic aperture radar (SAR) remote sensing data have been widely leveraged in disaster monitoring, environmental monitoring, resource exploration, and agricultural planning, etc. [1][2][3][4]. Optical remote sensing image data are more representative of what we can observe with the naked eye, which means that these data contain rich spectral information, but capture depends heavily on the clarity of the environment.…”
Section: Introductionmentioning
confidence: 99%